AB1412-HPR Is diffuse alveolar haemorrhage in anca- associated vasculitis predictive of poor prognosis?. (12th June 2018) - Garcia, L.; Pena, C.; Aguila Maldonado, R.; Costi, A.C; Testi, A.; Nagua, V.; Garcia, M.A.
Abstract : Background: Diffuse alveolar haemorrhage (DAH) is a serious complication of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). Detailed characteristics of patients with AAV and associated DAH have been limited to case reports and a few case series, due to the rarity of the condition(. 1 Prompt diagnosis is required as early treatment is crucial. Objectives: To compare clinical manifestations, laboratory and inmunological values, morbidity and mortality in patients with ANCA-associated vasculitis (AAV) with and without Diffuse Alveolar haemorrhage (DAH) Methods: Retrospective cohort study. Data from the medical records of patients over the age of 18 were evaluated between the years 2000–2017. Ninety patients with diagnosis of AAV who met the criteria of ACR 1990 Classification or Chapel Hill Concensus Conference 2012 were included. DAH was diagnosed based on minor or major hemoptysis and/or respiratory insufficiency together with at least 1 positive result on x-ray and/or computed tomography scan. The sample was divided in two groups: with DAH (group 1) and without DAH (group 2) along the disease. We compared demographic data, Birmingham Vasculitis Activity Score (BVAS) and Five Factor Score (FFS) at the onset of the desease, hemogram, creatinine and ANCA antibodies by inmunofluoresence and/or ELISA, clinical manifestations as renal, neurological, mucocutaneous, articular, cardiological, oftalmological and ear, nose and throat (ENT) damage and mortality between groups. Chi-square or Fisher's exact test was used for dichotomous variables as appropriate. P-value<0.05 was considered statistically significant. Logistic regression analysis was used to identify predictors of survival. Results: Group 1 included 24 patients (66% male, mean age at onset of the disease 54 years). Most frequent type of vasculitis was Granulomatosis with polyangeitis (GPA) 54%. Mean BVAS 21 points and FFS 1 point. Group 2 included 66 patients: 36% male, mean age of the desease 52 years, GPA 45%, BVAS was 17 points and FFS de 0 points. Table 1 shows demographic, clinical data and mortality of each group. Logistic regression analysis showed statistically significant difference between DAH and male sex (p: 0.017 OR 6.08 CI 95% 1.37–26.92). Conclusions: DAH was associated with increased morbidity but not modified the mortality in this group of patients. The results seem to be agree on the Five Factor Score 2 that does not include DAH within parameters. References: [1] West, S, et al. Diffuse Alveolar Haemorrhage in ANCA-associated Vasculitis. Intern Med52: 5–13, 2013. [2] Guillevin, L, et al. The Five- Factor Score revisited: assessment of prognoses of systemic necrotizing vasculitides based on the FVSG cohort. Medicine (Baltimore)2011; 90: 19–27. Disclosure of Interest: None declared